Mineral composition of important shell fish species from the Escravos River Estuary, Delta State, Nigeria and their nutritional significance. - Eyo, Victor Oscar; Ajang, R.; Ewutanure, S. J.; Eriegha, Ochuko Joshua; Eze, Felix; Udobong, Bridget Effiong (Journal of Advances in Food Science and Technology, 2023)
This study was conducted to evaluate the mineral composition (phosphorus, sodium, potassium, magnesium, calcium, iron, copper, manganese and zinc) of important shell fish species from the Escravos River Estuary, Delta State, Nigeria. A total of five shell fish species including the Pink shrimp (Peneaus notialis), Tiger shrimp (Peneaus monodon), Blue crab (Callinectes amnicola), Perewinkle (Tympanostonus fuscatus), and Mangrove oyster (Crassostrea gasar) were collected and used for the study. The shell fishes were collected from the fish landing sites of the estuary between March 2022 and June 2022 and analyzed for mineral composition following standard methods. The findings of this study showed that all the shell fish species evaluated were rich in minerals including phosphorus (P), sodium (Na), potassium (K), magnesium (Mg), calcium (Ca), iron (Fe), copper (Cu), manganese (Mn) and zinc (Zn) which varied significantly (P<0.05) among the shell fish species. This is the first study to evaluate the mineral composition of important shell fish species that are of particular public health significance in the Escravos river estuary. The findings of this study have provided baseline information or database of minerals in shell fishes from the Escravos River. Therefore, shell fish consumers within the Escravos river will be sufficiently knowledgeable on the mineral composition of each shell fish species examined with the flexibility of consuming the shell fishes according to their mineral need. Also, the mineral profile of these shell fishes would provide a guideline for nutritionists and medical practitioners in the prescription of diet charts for the inhabitants of the Escravos river estuary and beyond.
Keywords: Mineral content; Escravos River Estuary; health significance; Diets.